Vegetation and soil seed bank relationships across microhabitats in an abandoned Quercus suber parkland under simulated fire - Torres, Ivan; Urbieta, Itziar R; Moreno, Jose M (Ecoscience, 2012)
Mediterranean agro-forestry systems are undergoing rapid change due to abandonment. This turns formerly cultivated or grazed oak-tree parklands (i.e., savanna-type formations called “dehesas”) into flammable formations of scattered trees within a matrix of shrubs with open spaces. Wildfires can now occur, threatening the persistence of these formations. Fire-prone shrublands commonly regenerate after fire from seeds stored in the soil. Understanding the relationships between standing vegetation and the soil seed bank across microhabitats can help predict the response of the system in case of fire. Here we investigated these relationships in an abandoned Quercus suber (cork oak) dehesa in central Spain. Vegetation and soil were sampled and assigned to different microhabitats: under the trees (TRC), in dense shrub cover (DSC), and in low shrub cover (LSC). A heat shock was applied to half of each sample to simulate fire; the other half served as control. Both sets of samples were then germinated in a greenhouse. Almost 90% of the species were herbs, while the rest were woody shrubs. The number of species recorded in TRC and DSC was lower than in LSC, in which species richness, particularly herbs, was maximal. Heating increased the total number of species that germinated, but mean species richness per sample was not altered. Heating markedly increased the number of germinations in all microhabitats, particularly those of woody species. Furthermore, the germination of shrubby species increased in the 3 microhabitats, notably in TRC. While the standing plant community was well differentiated among microhabitats, this was not the case for the soil seed bank, which was homogeneous across microhabitats, with or without heating. We conclude that the high density of shrubby seeds found in TRC or in the other microhabitats presents substantial threats to the persistence of Q. suber parklands in case of fire.
Keywords: cistus; Cork oak; Dehesa; Encroachment; Erica; Mediterranean shrublands

Phenological pattern of fifteen Mediterranean phanaerophytes from shape Quercus ilex communities of NE-Spain - Pilar, C D; Gabriel, M M (Plant Ecology, 1998)
The phenological pattern of ﬁfteen Mediterranean phanaerophytes has been studied in several sites per species, by visiting the populations on a monthly basis over a one year period. Studied phenophases were dolichoblast vegetative growth (DVG), ﬂower bud formation (FBF), ﬂowering (F), fruit setting (FS), seed dispersal (SD), and leaf shedding of dolichoblasts (LSD). Considering the whole set of species, DVG, FBF and F took place mainly in spring, FS in summer, SD in autumn and LSD in summer and in autumn. Interspeciﬁc comparisons showed a wide variety of phenological patterns, which have been sorted according to the ‘phenophase sequence index’ (PSI). This index quantiﬁed the degree of superposition between DVG, FBF and F, and it constituted the basis for a functional classiﬁcation of phenological patterns. Two groups were established. The ‘type I’ group was characterised by the concentration of phenophases in a short time in spring, while the ‘type II’ by the protraction and sequential arrangement of phenophases. Type I species performed most of their functions during a resource surplus period, but they have to face an intraplant competition between vegetative and reproductive demands. Type II species avoided intraplant competition but had to develop part of DVG, FBF and F during sub-optimal periods. It is hypothesised that type I species possess deeper roots, rely on predictable water sources and occupy mature stages of succession. Type II species, on the contrary, are expected to depend on more unpredictable water sources, to possess shallower root systems and to colonise earlier stages of succession. Intraspeciﬁc variability of phenology was found to be low among populations of the same species. Bud structure, which is a phylogenetic trait, may exert important constraints on plant phenology
Keywords: annual cycle; bud type; Mediterranean shrublands; phenophase sequence index